Effect of supplemental oxygen exposure on myocardial injury in ST-elevation myocardial infarction. Issue 6 (6th January 2016) - Nehme, Ziad; Stub, Dion; Bernard, Stephen; Stephenson, Michael; Bray, Janet E; Cameron, Peter; Meredith, Ian T; Barger, Bill; Ellims, Andris H; Taylor, Andrew J; Kaye, David M; Smith, Karen
Abstract : Objective: Supplemental oxygen therapy may increase myocardial injury following ST-elevation myocardial infarction (STEMI). In this study, we aimed to evaluate the effect of the dose and duration of oxygen exposure on myocardial injury after STEMI. Methods: Descriptive analysis of data from a multicentre, prospective, randomised, controlled trial of 441 patients with STEMI randomised to supplemental oxygen therapy or room air breathing. The primary endpoint was myocardial infarct size as assessed by cardiac biomarkers, troponin (cTnI) and creatine kinase (CK). Oxygen therapy was commenced by paramedics, and continued for up to 12 h postintervention in hospital. Supplemental oxygen exposure was calculated as the area under the dose×time curve for oxygen administration over the first 12 h, and then assessed for its association with cTnI/CK release using multivariable linear regression. Results: The median supplemental oxygen exposure was 1746 L (IQR: 960–2858). After adjustment for potential confounders, every 100 L increase in oxygen exposure in the first 12 h was associated with a 1.4% (95% CI 0.6% to 2.2%, p<0.001) and 1.2% (95% CI 0.7% to 1.8%, p<0.001) increase in the mean peak cTnI and CK, respectively. Excluding patients who developed cardiogenic shock, recurrent myocardial infarction or desaturations (SpO2 <94%) during admission, every 100 L increase in oxygen exposure was associated with a 1.2% (95% CI 0.2% to 2.1%, p=0.01) and 1.0% (95% CI 0.3% to 1.7%, p=0.003) increase in the mean peak cTnI and CK, respectively. The median supplemental oxygen exposure of 1746 L would result in a 21% (95% CI 3% to 37%) increase in infarct size according to the cTnI profile. Conclusions: Supplemental oxygen exposure in the first 12 h after STEMI was associated with a clinically significant increase in cTnI and CK release.